A Controlled Gas-based Dehydrator for Drying Bananas in The Home Industry - Amri, Iful; Kurniawan, Sigit; Gunova, Violla; Arianza, Yumi; Parida, Della Exsal (Universitas Telkom, 2023)
In order to increase the durability and quality of bananas, this research discusses the design of an economical gas-based dehydrator with the application of PID control for valves and gas, specifically for small and medium-scale home industries. The main objective was to develop a cost-effective and efficient solution for drying bananas without sacrificing nutritional quality and taste. The dehydrator system is designed using PID control to obtain accurate and precise temperatures during the drying process. The algorithm is that the PID control will regulate and adjust how much gas is released through the valve based on the difference between the desired and actual temperature in the drying room. The best constants of PID we get are P = 1, I = 2, and D = 3. By applying these constants, the time taken by the system to change a signal from 30oC to 100oC of temperature is about 5 minutes, with a maximum overshoot of about 10%. In addition, the system required 25 minutes to achieve a steady state with an error value of about 5% from the setpoint. From the results of this experiment, it would be declared that the performance of the dehydrator built has indicated good performance. The minimum temperature that could be generated by the dehydrator is 90oC, while the maximum temperature is set 150oC. The experiment shows that this dehydrator can reduce the water content of a 1-2 g banana fruit by up to 50% within 60 minutes and 26% for a 10 g banana fruit mass simultaneously. The results also show that the dehydrator maintained optimal banana fruit quality based on texture, colour, and taste. Thus, these results indicate the great potential of gas-based dehydrators with PID control as an innovative solution for the home fruit processing industry, offering a combination of efficiency and cost-effectiveness